Small tea growers' perception towards Pricing of green tea leaf in Dibrugarh District of Assam - Phukan, Juri; Chakraborty , Deb Kumar (Indian Journal of Extension Education, 2026)
Tea cultivation on a small scale plays a crucial role in employment generation in rural areas of Assam and has contributed a lion’s share to the state's tea production. But the small tea growers (STGs) are facing many challenges, and a lack of fairness in the pricing of green tea leaves creates threats to their sustainability. The study assessed STGs’ perception towards the pricing of green tea leaves in Dibrugarh district of Assam.  379 samples were selected purposively from 3 tea-producing blocks of the district, and data were collected using a structured interview schedule. STGs’ perception towards pricing was examined with the help of a scale, calculated on the basis of 12 statements related to three approaches: distributive fairness, procedural fairness, and interactional fairness. The market of green tea leaves was dominated by the buyers, where the STGs play a minimal role in price realisation.51.72 % of STGs perceived the pricing of tea leaves as unfair, and 25.32% considered it highly unfair. Area of cultivation and the number of selling options were found to have a significant positive correlation with STGs’ perception. Initiatives to improve market infrastructure and automation of processing units are needed to ensure a fair pricing mechanism.